Path control of dexterous robotic hand using genetic algorithm - Albert F.Y.C.; Koh S.P.; Chen C.P.; Loo C.K.; Tiong S.K. (2023)
This paper would presents the path control of a dexterous robotic hand finger reaching in a given search space. The proposed system would adopt the advantages of Genetic Algorithm (GA) to optimize the system performance in terms of path control, speed and accuracy. The system would search for a valid path and optimal velocity. A new genetic operator, namely Real Coded Dynamic Multilayer Chromosome Crossover (RC-DMCC) has been introduced and incorporated in the system. The simulation results of the proposed technique are presented. 2009 IEEE.